How do you spell “freedom”? Narratives about the 25 April 1974 Revolution in the Brazilian press - Kieling, Camila Garcia (2018)
This paper proposes a recomposition of the intrigue of journalistic narratives on the Revolution of April 25, 1974 in Portugal based on the coverage of two Brazilian newspapers: O Estado de S. Paulo and Jornal do Brasil. The journalistic narrative is understood as a time orderer in the contemporaneity, expressing a “generalized circulation of historical perception” (Nora, 1979, p. 180), mobilized by the emergence of a new phenomenon: the event. The unusual coup d’état in Portugal stirred the world’s political imagination, reviving confrontations between left and right. At that moment, in Brazil, the military dictatorship completed 10 years and the fourth president of the Armed Forces was beginning its mandate. Narratives are analyzed from different points of view: the organization of facts in time, the construction of characters, projections for the future, or the re-signification of the past.